Análise dos critérios atendidos das NPT’S 011, 018 e 020 do código de segurança contra incêndio e pânico do corpo de bombeiros militar do Paraná (2014): estudo de caso em escolas municipais e casas noturnas - Secco, Jéssica (2014)
This project involves a research about Paraná's Fire Codes, focusing on the Technical Standards number 011, 018 and 020 - Emergency exits, Emergency Lighting and Emergency Signal Systems, respectively - with the aim of drawing up a checklist to be applied during construction inspections. The main focus are the Elementary Schools and Nightclubs located in the city of Pato Branco. From the analysis of the Technical Standards, the checklist was elaborated, resulting in 25 items and 215 sub-items, to be used to verify whether the fire codes are being correctly used or not at the buildings that were previously cited. Some visits were done at five Elementary Schools and three Nightclubs to verify the feasibility and the application of the checklist. It can be seen that there is a greater concern of all places make them safer, however, there are many points of the standard that must be adequate in these places, especially in public schools that have a larger number of items in disagreement with the providing for the safety standard fire and panic, as compared to nightclubs.